Eosinophilic esophagitis in children – current state of the problem - Buratynska, Antonina; Umanets, Tetiana; Lapshin, Volodymyr; Antipkin, Yurii (Pediatria Polska - Polish Journal of Paediatrics, 2019)
In recent years, eosinophilic esophagitis (EE) has become a general clinical problem for allergists and gastroenterologists. The prevalence of EE is two times more likely to occur in children than in adults. Despite the large number of studies, it is considered that the aetiology and pathogenesis of EE have not been completely determined. The peculiarity of EE is that inflammatory changes are focal and evenly cover the distal and proximal oesophagus. During the allergic inflammatory process of the epithelium the oesophagus acquires hyperplastic characteristics, which causes the accumulation of eosinophils within it. The clinical picture of EE is nonspecific and varies according to the child’s age and the degree of progression of the disease. It is known that the onset of EE in children or adolescents subsequently leads to the need for endoscopic and surgical correction of dysphagia, strictures, narrowing of the oesophagus in a low number of these patients.